Methodical Approach to the Analysis of Information Materials Regarding Public Discredit of the Use of the Armed Forces of the Russian Federation - T. N. Sekerazh (Теория и практика судебной экспертизы, 2022)
In view of the urgency of solving expert tasks resulting from the application of the new norms of the legislation of the Russian Federation regulating actions aimed at discrediting the use of the Armed Forces of Russia in order to protect the interests of the state and its citizens, maintaining international peace and security (Article 280.3 of the Criminal Code of the Russian Federation, Article 20.3.3 of the Administrative Code of the Russian Federation), the author reviews the methodical approach in the basis of the methodical letter for state forensic experts. The author justifies the expediency of appointing complex forensic psychological and linguistic examinations to analyze this kind of objects. She also presents the grounds for its appointment, the subject and objects, the tasks to be solved, and the main expert concepts of such examinations.